2020
DOI: 10.3390/microorganisms8101478
|View full text |Cite
|
Sign up to set email alerts
|

Canine Bone Marrow Mesenchymal Stem Cell Conditioned Media Affect Bacterial Growth, Biofilm-Associated Staphylococcus aureus and AHL-Dependent Quorum Sensing

Abstract: The present study investigated the in vitro antibacterial, antibiofilm and anti-Quorum Sensing (anti-QS) activities of canine bone marrow mesenchymal stem cell-conditioned media (cBM MSC CM) containing all secreted factors <30 K, using a disc diffusion test (DDT), spectrophotometric Crystal Violet Assay (SCVA) and Bioluminescence Assay (BA) with QS-reporter Escherichia coli JM109 pSB1142. The results show a sample-specific bacterial growth inhibition (zones varied between 7–30 mm), statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Another important difference between dog MSC and mouse and human MSC is that TLR3 activation of canine MSC had less impact on generation of direct antimicrobial activity, though it is important to note that TLR3 activation did significantly enhance the indirect antimicrobial properties of canine MSC. Although the levels of AMPs tested (LL37, HBD, SPD, Hapcidin, LCN) were not increased with TLR3 activation, a recent study examining antimicrobial properties of canine bone marrow derived MSCs ( 39 ) showed other classes of antimicrobial peptides such as apolipoprotein B and D, amyloid-β peptide, and S100-A4…etc. All of which have the potential to contribute to the direct antimicrobial activity; however full proteomic sequencing may be needed to determine the full continuum of peptides screted following TLR3 activation.…”
Section: Discussionmentioning
confidence: 90%
“…Another important difference between dog MSC and mouse and human MSC is that TLR3 activation of canine MSC had less impact on generation of direct antimicrobial activity, though it is important to note that TLR3 activation did significantly enhance the indirect antimicrobial properties of canine MSC. Although the levels of AMPs tested (LL37, HBD, SPD, Hapcidin, LCN) were not increased with TLR3 activation, a recent study examining antimicrobial properties of canine bone marrow derived MSCs ( 39 ) showed other classes of antimicrobial peptides such as apolipoprotein B and D, amyloid-β peptide, and S100-A4…etc. All of which have the potential to contribute to the direct antimicrobial activity; however full proteomic sequencing may be needed to determine the full continuum of peptides screted following TLR3 activation.…”
Section: Discussionmentioning
confidence: 90%
“…Again, canine BM-MSC-CM has shown in vitro activity against S. aureus biofilm and quorum sensing in Gram-negative bacteria [99]. A solid recent in vitro and in vivo study [87] reported that administration of MSCs as coadjuvant to a conventional class of antibiotics, exerted a direct and indirect antimicrobial effect in a S. aureus mouse infection.…”
Section: Mscs As Source Of Antibiotic-free Nanomaterialsmentioning
confidence: 99%
“…It should come as no surprise that these sources were also most common in this subset of studies. Ease of isolation was likely a factor in choosing BM or AT for some (Johnson et al, 2017;Cortés-Araya et al, 2018;Cahuascanco et al, 2019;Bujňáková et al, 2020;Peralta et al, 2020) and peripheral blood (PB) for others (Harman et al, 2017;Marx et al, 2020). Still, potency and lack of immunogenicity were also cited as reasons for choosing certain tissue sources, which led more than one group to isolate MSCs from fetal sources of BM, AT, or the amniotic membrane (Cahuascanco et al, 2019;Lange-Consiglio et al, 2019;Peralta et al, 2020).…”
Section: Examples Of Antimicrobial Effect Of Msc In Domestic Animals mentioning
confidence: 99%
“…Consequently, the secretome can be influenced by culture conditions that activate or precondition MSCs to respond to the clinical problem at hand as discussed above. In the articles reviewed here, only two of the studies took strictly a cellular approach (Johnson et al, 2017;Peralta et al, 2020), one assessed both cells and CM (Harman et al, 2017), while the rest worked only with CM (Cortés-Araya et al, 2018;Cahuascanco et al, 2019;Lange-Consiglio et al, 2019;Bujňáková et al, 2020;Marx et al, 2020). Co-culturing equine PB-MSCs with either E. coli or S. aureus, Harman et al compared direct contact with transwell separation and found that both the cells and the paracrine factors alone had an inhibitory effect albeit somewhat muted in the case of the transwell setup (Harman et al, 2017).…”
Section: Examples Of Antimicrobial Effect Of Msc In Domestic Animals mentioning
confidence: 99%